Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2001
DOI: 10.1115/2001-gt-0299
|View full text |Cite
|
Sign up to set email alerts
|

The Periodical Interaction of the Tip Clearance Flow in the Blade Rows of Axial Compressors

Abstract: Current models on the tip clearance flow in turbomachines only describe the time-averaged behaviour of the flow structures. However, the real tip clearance flow is periodically fluctuating in time. This fact has to be considered for the design of turbomachine bladings especially with regard to blade vibrations and tip clearance noise. Detailed experimental investigations on the time-resolved behaviour of the flow in the rotor blade tip region were carried out in a four-stage low-speed research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 0 publications
7
19
0
Order By: Relevance
“…As already found in axial compressors [9][10][11][12][13][14], when the mass flow rate is below a certain value the tip leakage flow begins to fluctuate at some frequencies. Especially within a narrow operating range near the stability limit when the compressor has a relatively large tip clearance, a unique phenomenon namely rotating instability occurs, which has been observed in axial and centrifugal compressors.…”
Section: Frequency Characteristic Of Tip Leakage Vortexsupporting
confidence: 62%
See 2 more Smart Citations
“…As already found in axial compressors [9][10][11][12][13][14], when the mass flow rate is below a certain value the tip leakage flow begins to fluctuate at some frequencies. Especially within a narrow operating range near the stability limit when the compressor has a relatively large tip clearance, a unique phenomenon namely rotating instability occurs, which has been observed in axial and centrifugal compressors.…”
Section: Frequency Characteristic Of Tip Leakage Vortexsupporting
confidence: 62%
“…This paper will concentrate on the development of rotating stall from normal operating conditions to stalled condition in a centrifugal compressor with vaned diffuser and try to explain the reason for the formation of rotating stall. In the process some interesting phenomena similar to the rotating instability found and investigated by Mailach [9,10] and Marz [11] et al in axial compressors are presented here. Whether this phenomenon is a precursor of rotating stall is still a problem under research.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Numerous other researchers have studied the NSV problem in turbomachinery and one particular area that has received considerable interest is tip flow instability. Examples of work in this area can be found in Mailach (1999), Mailach et al (2000Mailach et al ( & 2001, Marz et al (1999), Inoue et al (1999, Lenglin &Tan (2002), andVo (2001). Mailach et al (2001) Camp (1999) reports that this vexing problem has been observed in a high speed compressor.…”
Section: Figure 1 Hypothetical Campbell Diagram Demonstrating Designmentioning
confidence: 99%
“…Examples of work in this area can be found in Mailach (1999), Mailach et al (2000Mailach et al ( & 2001, Marz et al (1999), Inoue et al (1999, Lenglin &Tan (2002), andVo (2001). Mailach et al (2001) Camp (1999) reports that this vexing problem has been observed in a high speed compressor. As a result, an experimental study was performed in a low speed compressor facility.…”
Section: Figure 1 Hypothetical Campbell Diagram Demonstrating Designmentioning
confidence: 99%